Optimization of the operating variables for the extraction of soy oil in a single screw expeller using a central composite design (CCD) - Aremu, Mujidat Omolara (Array, 2019)
Steam pressure (P) and toasting time (T) were considered under the Central Composite Design (CCD) for the optimization of oil and cake yield, as well as trypsin inhibitor and phosphorus content removal from soybean during the extraction process in the expeller machine. The soy oil was characterized for its acid, iodine, and peroxide values. The obtained optimized experimental condition [Run 11 (2.50 kg/ms2 and 60.00 min)] resulted in 80%, 13 L/100 kg, 0.266 mg/g, and 0.39 mg/g cake yield, oil yield, trypsin inhibitor (TI), and phosphorus concentrations (PC), respectively. The correlation coefficients (R2) of the model equation developed for cake yield, oil yield, TI concentrations, and PC were 0.9922, 0.9545, 0.9747, and 0.6771, respectively. The peroxide, acid, and iodine values of the soy oil extracted were 18 meq O2/kg oil, 1.60 mg KOH/g oil, and 60.40 g/100 g, respectively. The optimisation tools facilitated the efficiency of the expeller in generating better products.